2012
DOI: 10.1264/jsme2.me11348
|View full text |Cite
|
Sign up to set email alerts
|

Production and Consumption of Hydrogen in Hot Spring Microbial Mats Dominated by a Filamentous Anoxygenic Photosynthetic Bacterium

Abstract: Microbial mats containing the filamentous anoxygenic photosynthetic bacterium Chloroflexus aggregans develop at Nakabusa hot spring in Japan. Under anaerobic conditions in these mats, interspecies interaction between sulfate-reducing bacteria as sulfide producers and C. aggregans as a sulfide consumer has been proposed to constitute a sulfur cycle; however, the electron donor utilized for microbial sulfide production at Nakabusa remains to be identified. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…Earlier studies have also reported H 2 formation in hot spring microbial mats, where H 2 production may be due to fermentation (18,19,22,36) or to formation as a by-product of nitrogenase activity during N 2 fixation (30). The relative importance of these processes for H 2 dynamics in hot spring cyanobacterial communities has remained unclear, while studies of hypersaline and coastal cyanobacterial mats have identified fermentation as the major H 2 source (7-9).…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies have also reported H 2 formation in hot spring microbial mats, where H 2 production may be due to fermentation (18,19,22,36) or to formation as a by-product of nitrogenase activity during N 2 fixation (30). The relative importance of these processes for H 2 dynamics in hot spring cyanobacterial communities has remained unclear, while studies of hypersaline and coastal cyanobacterial mats have identified fermentation as the major H 2 source (7-9).…”
Section: Discussionmentioning
confidence: 96%
“…Our results are consistent with a recent lipid biomarker study where glycerol dialkyl glycerol tetraether from spring sediments were distinctly different from surrounding soils (Wu et al, personal communication). These heterotrophs occurring in August grew either by anaerobic respiration (such as Desulfococcus 36, Acidicladus 57 and Desulfurella 44 using sulfate, ferric iron and sulfur as an electron acceptor, respectively) or fermentation (such as Ignisphaera 41, Thermus 58, Fervidobacterium 15, Sulfophobococcus 43 and GAL3532). These physiological characteristics suggest that they may have initially inhabited heterogeneous and anaerobic micro-environments within spring sediments in January, but when the conditions became favorable (e.g., high TOC and nutrients), these minor microbes may have flourished and even become predominant.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial censuses of microbial community structure have been well-studied in diverse hot springs12345678 and these studies have shown that physicochemical parameters of hot springs such as temperature, pH and nutrient supply are important drivers for shaping microbial diversity and community structure as well as metabolism45910111213141516. In contrast, only a limited number of studies in the last decade have explored temporal changes in hot spring communities1718192021, but similar conclusions have been made that temporal changes in microbial community are correlated with temporal variations of temperature18, pH20, and nutrient availability1821.…”
mentioning
confidence: 99%
“…A range of thermophilic microorganisms (~75-40°C) has been identified. Representatives of the bacterial phyla Cyanobacteria, Chloroflexi and Proteobacteria are the most commonly found microbes in neutral to alkaline hot springs (Otaki et al, 2012;Cole et al, 2013;Mackenzie et al, 2013;Wang et al, 2013). Within the cyanobacteria, unicellular members such as Synechococcus and Cyanothece typically dominate at temperatures above 60°C (Ward et al, 1998;Ward and Castenholz, 2000;Papke et al, 2003;Steunou et al, 2006Steunou et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…This process may represent an important source of 'new' nitrogen in the often nitrogenlimited hot spring waters. This process also counter acts the loss of combined nitrogen caused by denitrification in the poorly ventilated substrates of terrestrial hot springs (Otaki et al, 2012). N 2 fixation has been assessed by screening for specific nif genes such as nifH (encoding the α-subunit of the nitrogenase enzyme complex), which is the most widely used molecular marker in the search for diazotrophs.…”
Section: Introductionmentioning
confidence: 99%